Evaluation of Black Cumin (Nigella sativa L.) Genotypes for Yield and Yield Related Parameters in Potential Growing Areas of Ethiopia - Fikre, Demis; Mengistu, Fekadu Gebretensay; Tsagaye, Dasta; Ali, Awoke; Fufa, Nimona; Wegayehu, Gizaw (International Journal of Bio-resource and Stress Management, 2023)
Multi-environment trials were carried out at 3 locations in different black cumin growing zones of Ethiopia during June-December, 2017–2018 and 2018–2019 to select high yielding and adaptable genotypes for commercial production in Ethiopia. Ten advanced black cumin genotypes were evaluated with one standard check variety. The genotypes were arranged in Randomized Complete Block Design with three replications. The ANOVA revealed that the differences in seed yield among genotypes (G), environments (E) and genotype by environment interaction (GEI) were highly significant (p<0.01). Besides, significant (p<0.01) differences were obtained for days to 50% flowering, days to maturity, plant height, number of pod plant-1, number of seeds pod-1, seed yield plant-1, and thousand seed weight. However, days to emergence, number of primary and secondary branches plant-1 were not significant (p>0.05). The highest seed yield was recorded from genotype 242840 (1102 kg ha-1) followed by 242841(1038 kg ha-1) and these genotypes had 35% and 26.39% yield advantage over the check variety-Aden respectively. Moreover, the two genotypes were better in oleoresin content among others. The partitioning of GE through GGE biplot analysis showed that PC1 and PC2 accounted for 47.09% and 18.18%, explaining 65.27% of the total variance. The GGE biplot ranked the genotypes for yield performance; the genotypes viz. 24840 and 24841 were among the five marker (winning) genotypes and showed their wider adaptability across the testing environments. Therefore, the genotypes were selected as potential candidate genotypes for on farm verification and possible release for commercial production in the testing environments and similar agro ecologies.